2015
DOI: 10.1002/art.39030
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Prg4‐Expressing Articular Cartilage Progenitor Cell Population in Mice

Abstract: Objective We generated knock-in mice that express a tamoxifen-inducible Cre recombinase from the Prg4 locus (Prg4GFPCreERt2), and used these animals to fate-map the progeny of Prg4-positive articular cartilage cells at various ages. Methods We crossed Prg4GFPCreERt2 mice to Rosa26floxlacZ or Rosa26mTmG reporter strains, administered tamoxifen to the double heterozygous offspring at different ages, and assayed Cre-mediated recombination by histochemistry and/or fluorescence microscopy. Results In 1-month-ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
239
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 201 publications
(262 citation statements)
references
References 30 publications
11
239
4
Order By: Relevance
“…Previous studies with chondrocyte-specific knockout of Mig-6 (10-12) also support our conclusion, as young mice exhibit hyperproliferation and hypercellularity in the top part of articular cartilage. A recent study identified Prg4-expressing cells located at the cartilage surface as chondrogenitors for deeper layers of the mature articular cartilage (19). We also observed a decrease in chondrocyte cellularity in an uncalcified area below the superficial layer, accompanied with an increase in the percentage of hypertrophic chondrocytes.…”
Section: Discussionsupporting
confidence: 72%
“…Previous studies with chondrocyte-specific knockout of Mig-6 (10-12) also support our conclusion, as young mice exhibit hyperproliferation and hypercellularity in the top part of articular cartilage. A recent study identified Prg4-expressing cells located at the cartilage surface as chondrogenitors for deeper layers of the mature articular cartilage (19). We also observed a decrease in chondrocyte cellularity in an uncalcified area below the superficial layer, accompanied with an increase in the percentage of hypertrophic chondrocytes.…”
Section: Discussionsupporting
confidence: 72%
“…We compared measures of cell number and the number of nuclei in the imaged cartilage volume (cell density) between an individual animal's left and right limbs and between the limbs of surface of articular cartilage (20 cell number or cell density, we measured the same specimens at weekly intervals ( Figure 1H and Supplemental Figure 4) and observed no systematic differences (Supplemental Figure 4 and Supplemental Table 2). …”
Section: Resultsmentioning
confidence: 98%
“…Mice that have a cDNA encoding a chimeric GFPCreERt2 protein knocked into the first coding exon of Prg4 can have Crerecombinase activity induced in most chondrocytes near the (10,20,30, and 40 μm) in control mice (C) and DTA-ablated mice (D) identify DAPI-stained chondrocyte nuclei (blue), nonrecombined membraneanchored dTomato-expressing chondrocytes (red), and Cre-recombined membrane-anchored eGFP-expressing chondrocytes (green). Identical thresholds were employed for all images.…”
Section: Resultsmentioning
confidence: 99%
“…Given our findings that interfering with p16 INK4a expression did not alter SASP production, investigating p16 INK4a loss in cell types with greater proliferative potential than chondrocytes may be of interest. For example, synovial fibroblasts and progenitor cells in the superficial zone of cartilage could be targeted for p16 INK4a loss with the Prg4 tm1(GFP/cre/ERT2)Abl allele (Kozhemyakina et al., 2015). Lineage tracing studies have suggested that subpopulations of synovial cells harbor regenerative potential (Decker et al., 2017) and a proliferative block in these cells through senescence may limit this capacity with aging.…”
Section: Discussionmentioning
confidence: 99%